Model and data engineering First International Conference, MEDI 2011, Óbidos, Portugal, September 28-30, 2011. Proceedings - Bellatreche, Ladjel; Mota Pinto, Filipe (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the First International Conference on Model and Data Engineering, MEDI 2011, held in Óbidos, Portugal, in September 2011. The 18 revised full papers presented together with 8 short papers and three keynotes were carefully reviewed and selected from 67 submissions. The papers are organized in topical sections on ontology engineering; Web services and security; advanced systems; knowledge management; model specification and verification; and models engineering.